The Effect of Antenatal Diaphragmatic Breathing Exercise in Preventing Decreased Uterine Contractions in Caesarean Section Patients - Euis Tuti Haryani; Restuning Widiasih; Murtiningsih Murtiningsih; Yayat Suryati; Siti Nurbayanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
The number of sectio caesarea (sc) deliveries has increased, the main side effect of sc is bleeding caused by inadequate contractions. Understanding the risk of atony management is very important starting from antenatal care, various education is given to mothers including doing aerobic exercises including diphragmatic breathing as a prevention of uterine atony. The aim of this study was to see the effect of antenatal diaphgramatic breathing (dbe) exercise on preventing a decrease in uterine contractions in CS patients. This research method used a quasi-experimental posttest nonequivalent design with control group design, the sample in this study were 3rd trimester pregnant women who were at risk of being elective, totaling 56 people by using incidental sampling techniques, using the uterine contraction observation sheet instrument, data analysis used the chi square test. The results of the study showed that there was a significant effect of antenatal dbe implementation on preventing a decrease in intraoperative uterine contractions after the placenta came out. However, there was no effect of antenatal dbe on preventing uterine contractions 1-2 postoperative sc.